2018
DOI: 10.1002/chem.201801387
|View full text |Cite
|
Sign up to set email alerts
|

N4‐Tetradentate Chelators Efficiently Regulate Copper Homeostasis and Prevent ROS Production Induced by Copper‐Amyloid‐β1–16

Abstract: The disruption of copper homeostasis and the oxidative stress induced by Cu-amyloids are crucial features of Alzheimer's disease pathology. The copper specific N -tetradendate ligands TDMQ20 and 1 are able to fully inhibit in vitro the aerobic oxidation of ascorbate induced by Cu-Aβ , even in the presence of 100 molar equivalents of Zn with respect to Cu , whereas other ligands with N O or N O coordination spheres failed to do so. This essential result indicates that, in addition to metal selectivity, the coor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 32 publications
2
32
1
1
Order By: Relevance
“…In vitro, TDMQ20 and 1 are able to immediately and completely stop the ongoing aerobic oxidation of ascorbate induced by Cu-Ab1-16, even in the presence of 100 mol equiv of Zn(II) with respect to copper (Figure 5), while a reduced Schiff base ligand with a N2O2-coordination sphere, or PBT2 (whose copper complex has a metal/ligand stoichiometry = 1/2, and a N3O2-coordination sphere) failed to inhibit the dioxygen reduction either in the presence or in the absence of zinc. 82 In addition, TDMQ chelators (up to millimolar concentrations) do not affect in vitro the catalytic activities of Cu,Zn-superoxide dismutase and tyrosinase, two copper enzymes expressed in the brain and involved in the regulation of redox processes. 84 The preliminary data on in vitro metabolism by microsomes and caco-2 underlines the druggability of the TDMQ ligands (unpublished data).…”
Section: Physiological Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro, TDMQ20 and 1 are able to immediately and completely stop the ongoing aerobic oxidation of ascorbate induced by Cu-Ab1-16, even in the presence of 100 mol equiv of Zn(II) with respect to copper (Figure 5), while a reduced Schiff base ligand with a N2O2-coordination sphere, or PBT2 (whose copper complex has a metal/ligand stoichiometry = 1/2, and a N3O2-coordination sphere) failed to inhibit the dioxygen reduction either in the presence or in the absence of zinc. 82 In addition, TDMQ chelators (up to millimolar concentrations) do not affect in vitro the catalytic activities of Cu,Zn-superoxide dismutase and tyrosinase, two copper enzymes expressed in the brain and involved in the regulation of redox processes. 84 The preliminary data on in vitro metabolism by microsomes and caco-2 underlines the druggability of the TDMQ ligands (unpublished data).…”
Section: Physiological Functionmentioning
confidence: 99%
“…This copper transfer is fully effective even in the presence of an excess of Zn(II) ions, mimicking the zinc-rich environment of the brain. 82 TDMQ20 or TDMQ22 can be considered as lead molecules. As the above mentioned bis(8amino)quinoline 1, TDMQ20 (Figure 1) Both TDMQ20 and 1 specifically chelate Cu(II) in a nearly perfect N4-square planar fashion (Figure 4), with a poor capacity to fit with the preferred tetrahedral coordination requested for Cu(I).…”
Section: Physiological Functionmentioning
confidence: 99%
“…, and this catalytic activity has been correlated to their redox potential and coordination chemistry [76, 77] . The in vitro ROS production of Cu complexes of CarHQs and the parent compounds Car and HQ was evaluated through the kinetics of AA oxidation, as monitored by UV/Vis spectroscopy, as typically reported (Figure S44 in the Supporting Information) [78–80] …”
Section: Resultsmentioning
confidence: 95%
“…[76,77] The in vitro ROS production of Cu complexes of CarHQs and the parentc ompounds Car and HQ was evaluated through the kinetics of AA oxidation, as monitored by UV/Vis spectroscopy,a st ypically reported ( Figure S44 in the Supporting Information). [78][79][80] The rate (V 0 )o fA Ac onsumption ( Figure 8B)i si ndicative of the ability of the Cu speciest oproduce ROS.…”
Section: Inhibition Of Cu-ab Ros Production By Carhqsmentioning
confidence: 98%
“…[37,38] Moreover, it has been reported that N 4 -tetradentate ligands inhibit the aerobic oxidation of ascorbate induced by CuÀ Aβ 16 in a Zn-rich environment. [39] The authors, comparing different chelators with N 4 , N 2 O 2, and N 3 O 2 coordination sphere, conclude that chelators should exhibit an N 4 -tetradentate motif to selectively target Cu and inhibit the ROS production caused by Cu-bound Aβ species. [39] Here, we demonstrate that the N 4 -tetradentate motif is not crucial for the selective extraction of Cu from Aβ species.…”
Section: Introductionmentioning
confidence: 99%